REGRET IN NICHOLAS SPARKS’ NOVEL THE BEST OF ME - Anggi Pangestina; Devi Pratiwy (Universitas Islam Sumatera Utara, 2022)
This study aims to discuss the types of regret that represent the effects of the protagonist's regret in Nicholas Spark's novel entitled The Best of Me, and to describe the effects of the protagonist's regret. This study is the result of a qualitative assessment of the regrets of the protagonist named Dawson Cole. The theory used in this study is the theory proposed by Zeelenberg (2007), and supported by Pieters R. A (2007). The results of this study indicate that there are two types of regret reflected in the novel; they are existential regret and regret of inaction. The cause of the protagonist's regret is that the protagonist avoids Amanda all his life, and his regret that he is inferior and unworthy to be with Amanda. The effect of the protagonist's regret is that he lies to his own feelings and remains single for the rest of his life.